Regeneration of Shorea spp. in the Seed Sources of KHDTK Haurbentes. Bogor District - Kurniawati Purwaka Putri; Dede J. Sudrajat (Jurnal Perbenihan Tanaman Hutan, 2017)
The role and function of forest area with special purpose (KHDTK) Haurbentes among other are the source of seeds and germplasm of Shorea spp. The information of the potency and dominance of Shorea spp. in KHDTK Haurbentes was indispensable in formulating the seed source management strategy. The aim of the research was to determine the regeneration level of Shorea spp. in Haurbentes KHDTK. The research was conducted in KHDTK Haurbentes in Jasinga, Bogor District. The research method used vegetation analysis. Observation plots were built based on the design of cluster plot Forest Health Monitoring circular (annular plot). Number of cluster plot of 6 pieces was set purposively. The results showed that S. pinanga was dominant species for the level of the tree, pole, sapling and seedling in cluster plots 1 and 7. The vegetation of trees level were dominated by S. stenoptera (cluster plots 2, 6, 8) and S. selanica (cluster plot 3). Vegetation of pole level were dominated by S. stenoptera (clusters plots 6 and 8) and S. selanica (cluster plots 2 and 3). H. mangarawan and S. mecisopteryx were dominant species for the level of sapling in clusters plot 6 and 8. Peuris and harendong (Melastoma polyanthum Bl) were dominant species at sapling level in cluster plots 2 and 3 for shrubs, while for species of shorea, the dominant species were S. stenoptera (clusters plots 2) and S. selanica (clusters plots 3). The dominant species at seedling level were H. mangarawan (clusters plot 2), S. mecisopteryx (clusters plot 3), S. selanica (clusters plot 6) and S. Stenoptera (cluster plots 8). The density of dominant species for the tree level was varied among cluster plots with a range of 55-143 individuals/hectare. Shorea spp. in KHDTK Haurbentes was sufficient with the number of individual regeneration more than adult trees. The sustainability of seed sources Shorea spp. in KHDTK Haurbentes in the future is quite assured.